Evaluation of English Learning In Junior High School Samaturu Kolaka - ., suardi (International Journal of Scientific Research and Management (IJSRM), 2020)
AbstractThe study aims to evaluate of english learning at the Junior High School 3, Samaturu Kolaka. The method used is evaluative through the flow of the gap model (discrepancy evaluation model). Data collection through interviews, document tracing, and observation. Key Informant is the principal, teacher, and student. The results showed that: (1). The ten indicators of the principles in the preparation of lesson plan is only a contemporary-oriented indicator that is not contained in the lesson plan. This is because lesson plan is based on teaching materials and teaching materials. In addition, the lesson plan does not promote social, spiritual attitudes and only focus on English language teaching materials. Because of social and spiritual attitudes are hidden curriculum and can be applied to all subjects. Even the development of character is a program of Junior High School 3, Samaturu Kolaka. (2). All step-by-step indicators in lesson plan preparation are already loaded inside the lesson plan. But there is still an unprecedented indicator such as determining a monotonous learning strategy and not self-evaluation for the teacher to improve the strategy, and its teaching method. (3). Several indicators of lesson plan implementation have been carried out well in the classroom even though it is not maximized. This is due to preliminary activities, the teacher does not explain the importance of the material to be studied and competencies that students must master. The conclusion is related to the principles, application of steps and implementation of lesson plan in the classroom, although not maximized, but has been referring to Permendikbud no. 103 year 2014 about learning on primary education and secondary education. Keywords: Evaluation, Lesson Plan, English Learning